Comparison of sagittal spinal alignment on standing plain x-rays and supine MRI in degenerative lumbar disease - Fan, Xiaolong; Xue, Deting; Pan, Zhijun; Wang, Yulu (Frontiers in Surgery, 2023)
Background: The purpose of the present study is to examine the possible correlation between standing plain X-rays and supine magnetic resonance imaging (MRI) for evaluating spinal sagittal alignment in degenerative lumbar disease (DLD). Methods: The characteristics and images of 64 patients with DLD were reviewed retrospectively. The thoracolumbar junction kyphosis (TJK), lumbar lordosis (LL) and sacral slope (SS) were measured on lateral plain X-rays and by MRI. Inter- and intra-observer reliability was tested using intra-class correlation coefficients. Results: The results suggested that TJK measurements obtained from MRI tended to underestimate the radiographic measures by 2°, whereas SS measurements obtained from MRI tended to overestimate the radiographic measures by 2°. The LL measurements obtained from MRI were approximately equal to the radiographic measures, and the X-ray and MRI measurements were linearly related. Conclusions: In conclusion, supine MRI can be directly translated into sagittal alignment angle measurements obtained from standing X-rays with an acceptable degree of accuracy. This can avoid the impaired view caused by the overlapping ilium, while reducing the patient’s exposure to radiation.